To solve algebraically, we multiply each element by the scalar multiplications and then add corresponding elements from A and B.
4A = 4 * [2 8 -3 -1 5 2] = [8 32 -12 -4 20 8]
3B = 3 * [-1 0 5 0 3 -2] = [-3 0 15 0 9 -6]
Then we add corresponding elements from 4A and 3B to get the final result:
4A + 3B = [8 32 -12 -4 20 8] + [-3 0 15 0 9 -6]
= [8 + (-3) 32 + 0 -12 + 15 -4 + 0 20 + 9 8 + (-6)]
= [5 32 3 16 29 2]
Therefore, 4A + 3B = [5 32 3 16 29 2].
if A=[2 8 -3 -1 5 2] and B=[-1 0 5 0 3 -2]
what is 4A+3B? Solve algebraically showing all steps
1 answer